STRUCTURAL AND OPTICAL CHARACTERIZATION OF ZnO FILMS DOPED WITH Ni - TOMA, M.; LUNG, C.; MARCONI, D.; POP, A. (Studia Universitatis Babeș-Bolyai Physica, 2018)
Zinc oxide (ZnO), and Ni-doped ZnO (NZO) thin films were deposited on glass substrates by radio frequency (RF) magnetron sputtering for three different distances between substrate-target. The influence of the distance between substrate-target upon structure of the thin films was analyzed by X-ray diffraction (XRD) and the grain size was determined by theoretical calculations. Optical transmission measurements show the influence of doping and distance between substrate-target on the optical band gap.